Effect of Docosahexaenoic acid (DHA) fortification in buffalo ghee during storage - Naagar, Sonam (Indian Journal of Dairy Science, 2017)
The present investigation was a maiden attempt to study the keeping quality of buffalo ghee by addition of algal oil (DHA) at 0.5% and 1% concentration in the presence of synthetic anti-oxidants viz. AP, BHA and TBHQ (200 ppm) by examining BR reading and free fatty acid (FFA) at 30°C and refrigeration temperature (8-10°C) during the storage period of 300 days. The effect of antioxidants on BR reading and FFA content of control ghee and DHA supplemented ghee was significant at 30°C while it was non-significant at 8-10°C. The effect of storage period on BR reading and FFA content of supplemented buffalo ghee at 30°C and 8-10°C was highly significant. The keeping quality of buffalo ghee was better by addition of DHA at 0.5% - 1% in the presence of synthetic anti-oxidant TBHQ followed by AP and BHA and within range specified by FSSAI Act (2006) and Rules (2011).